The Wiley handbook on offenders with intellectual and developmental disabilities : research, training, and practice - Lindsay, William R.; Taylor, John L. (John Lionel), 1961- (John Wiley & Sons, Inc., 2018)
The Wiley Handbook on Offenders with Intellectual and Developmental Disabilities is a comprehensive compendium to the research and evidence supporting clinical work with people with intellectual and developmental disabilities who offend or are at risk of offending. With contributions from an international panel of experts, the text reviews the most recent developments in the assessment, treatment and management of various types of offenders with intellectual disabilities including violent offenders, sexual offenders and firesetters. The text also explores the developments in research on risk assessment and management of people with intellectual disabilities who offend or are at risk of offending.